Affiliate Marketing In E-Commerce - A Comparative Study In The Retail And Telecommunication Sectors - Tan, Mei Woon (2005)
In this research project, a study on the affiliate marketing practices in e-commerce in Malaysia is done - the research emphasizes on the issues of how to determine whether the affiliate program is practised in the business and which group of business would apply this approach. There will be also be dircetion for the reader to focus on the content and develop the right affiliate model for the type of business.